Hadoop MapReduce cookbook. - Perera, Srinath (Packt Pub., 2013)
Individual self-contained code recipes. Solve specific problems using individual recipes, or work through the book to develop your capabilities. If you are a big data enthusiast and striving to use Hadoop to solve your problems, this book is for you. Aimed at Java programmers with some knowledge of Hadoop MapReduce, this is also a comprehensive reference for developers and system admins who want to get up to speed using Hadoop.
Author names from credits page.
Includes index.
Keywords: Apache Hadoop.; MapReduce.; Apache Hadoop; Electronic data processing -- Distributed processing.; Cluster analysis -- Data processing.; Open source software.; elektronické knihy; electronic books